Wpływ ustawodawstwa stanu wojennego na prawo cywilne w Polsce - Machnikowska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The author seeks to determine the impact of the legislation that emerged in connection with the introduction of martial law in Poland in 1981 on civil law. She starts by referring to axiology as well as the basic principles of civil law in the socialist state. This provides abackground for her discussion of the changes introduced after 13 December 1981. In her conclusion the author notes that even today there are still unresolved problems concerning damages and compensation for losses suffered during the martial law period by individuals who were interned as well as those who suffered injuries or were forced to emigrate. Some judges are not familiar with the legislation in force at the time and with the consequences of its application, as can be seen in rulings and statements of reasons dismissing some of the claims.
Keywords: socjalizm; komunizm; prawo cywilne; stan wojenny